2008
DOI: 10.1007/s11458-008-0021-4
|View full text |Cite
|
Sign up to set email alerts
|

Controlled/living photopolymerization of methyl methacrylate in miniemulsion mediated by HTEMPO

Abstract: Controlled/living photopolymerization of methyl methacrylate (MMA) in miniemulsion mediated by 4-hydroxy-2,2,6,6-tetramethyl-piperidinyloxy (HTEMPO) was carried out at ambient temperatures. MMA miniemulsion was prepared by using an anionic surfactant with cetylalcohol as a co-stabilizer. The photopolymerization led to stable lattices and they were obtained with no coagulation during synthesis and no destabilization over time. It was found that the obtained MMA homopolymers exhibited relatively narrow molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The ratio M w / M n found for these polymers varied from 2.3 to 3.5. This is in accordance with the nature of the free radical polymerization process . The presence of the mesogenic comonomer in the feed contributed to a significantly narrower molecular weight distribution in the resulting polymer in comparison to the neat non‐LC homopolymer poly(2‐EHA) ( M w / M n = 3.5).…”
Section: Resultssupporting
confidence: 78%
“…The ratio M w / M n found for these polymers varied from 2.3 to 3.5. This is in accordance with the nature of the free radical polymerization process . The presence of the mesogenic comonomer in the feed contributed to a significantly narrower molecular weight distribution in the resulting polymer in comparison to the neat non‐LC homopolymer poly(2‐EHA) ( M w / M n = 3.5).…”
Section: Resultssupporting
confidence: 78%
“…In view of the foregoing, the results of Chinese scientists seem amazing [ 72 ]. They managed to implement the emulsion photopolymerization of MMA using common nitroxide, 4-hydroxy-TEMPO, and photoinitiator Irgacure-184 at room temperature.…”
Section: Nitroxide-mediated Photopolymerizationmentioning
confidence: 99%
“…Even though neither nitroxide nor polymer contained chromophore groups, the authors observed a linear growth of M n of the polymer with conversion and Đ = 1.27–1.36. Unfortunately, the mechanism of photoinitiation was not discussed in [ 72 ].…”
Section: Nitroxide-mediated Photopolymerizationmentioning
confidence: 99%